Assessment of grain amaranth cultivation in advent of climatic change in Maharastra - Dua, R P; Kute, N S; Vane, Dattatraya (Indian Farming, 2015)
Agriculture is likely to be affected the most in advent of climate change putting poor people under stress. Before the major actions are taken to combat effects of climate change, it is essential to find out other suitable crops which are resilient and can diversify agriculture. Among food crops amaranth, a pseudo cereal and photo-insensitive crop is an important crop for such options. This can be used as a vegetable, food grain and for several other purposes. It has been found to be free from diseases and insects pests. It can withstand water stress and has been found to give good economic returns over wheat and gram during rabi season in Maharastra. In Gujarat state it has already become an important crop which replaces wheat and potato in water scant semi-arid areas.